Dual-functional gold–iron oxide core–satellite hybrid nanoparticles for sensitivity enhancement in biosensors via nanoplasmonic and preconcentration effects. Issue 22 (14th October 2021) - Chen, Yi-Chen; Chou, Yu-Chen; Chang, Jui-Han; Chen, Li-Ting; Huang, Chun-Jen; Chau, Lai-Kwan; Chen, Yen-Ling
Abstract : Using dual-functional gold–iron oxide core–satellite hybrid nanoparticles with magnetic preconcentration in the fiber optic nanogold-linked sorbent assay significantly improves the limit of detection. Abstract : A common strategy to improve the sensitivity of a biosensor for the detection of a low abundance analyte is to preconcentrate the analyte molecules before detection. A dual-functional gold–iron oxide core–satellite hybrid nanoparticle structure is proposed in this work to overcome the drawbacks of traditional sample pretreatment methods and the methods using non-magnetic nanomaterials for sample pretreatment. The new dual-functional hybrid nanoparticle structure can simultaneously serve as a signal reporter of a biorecognition event and a preconcentrator of a target at an extremely low concentration in a nanoplasmonic biosensor. By utilizing a fiber optic nanogold-linked sorbent assay in the fiber optic particle plasmon resonance (FOPPR) biosensor and an arbitrary DNA sequence as a target, we have demonstrated that the use of the new hybrid nanoparticle structure with magnetic preconcentration improves the limit of detection (LOD) for the DNA by 18 times as compared to the same method without magnetic preconcentration, so that the LOD for detecting the DNA can be as low as 2.6 fM. The new hybrid nanoparticle structure is easy to prepare and its use in the high-sensitivity and low-cost FOPPR biosensor provides vast opportunities in point-of-care applications.